Effectiveness of BNT162b2 vaccine against SARS-CoV-2 among healthcare workers : Effectiveness of HCWs vaccination against SARS-CoV-2 - Sansone, Emanuele; Sala, Emma; Tiraboschi, Mara; Albini, Elisa; Lombardo, Massimo; Indelicato, Annamaria; Rosati, Cristina; Boniotti, Maria Beatrice; Castelli, Francesco; De Palma, Giuseppe (La Medicina del Lavoro, 2021)
Background: The present study was aimed at evaluating the effectiveness of BNT162b2 among HCWs of a university hospital while a recrudescence of pandemics was hitting the province, with a high rate of the B.1.1.7 variant. Methods: The study was performed in the context of health surveillance at the workplaces. We monitored the SARS-CoV-2 infection and COVID-19 symptoms among HCWs classified by having received the entire vaccine schedule or not; the latter further classified in not vaccinated workers and workers who had received the first shot more than 14 days earlier. The SARS-CoV-2 infection was diagnosed by conventional RT-PCR on rhino-pharyngeal swabs, followed by gene sequencing in positive vaccinated HCWs. The cumulative incidence of infections in the period was normalised to 100,000 people. Results: At the end of the observation period, HCWs that had completed the full schedule were at lower infection risk than both unvaccinated HCWs and the workforce who had not yet gained the complete theoretical protection from the vaccine (by 2.4-folds). Overall, ninety-two SARS-CoV-2 infections were observed among HCWs, mostly among not protected workers (52 cases) but none of them showed symptoms requiring hospitalisation. Conclusions: The vaccination campaign effectively reduced the appearance of symptoms and the incidence of infections among vaccinated HCWs. Among vaccinated HCWs, gene sequencing was possible in five cases only, 4 B.1.1.7 and 1 B1.525 variants. The high rate of unsuccessful gene sequencing observed among infected vaccinated workers could be explained by a low viral burden. Vaccination for COVID-19 should be mandatory in occupational settings with a high infective risk.